Notary Deed in the Transfer of Rights to Local Government Assets - Fenny riska Diana; Benny Djaja (PT Publikasiku Academic Solution, 2023)
Based on the existing background, a formulation of the problem can be drawn, namely (1) what are the reasons for the prohibition of making authentic notary deeds outside the notary's office area? (2) What are the legal consequences for notary deeds made outside the notary's office area? The type in this research is to use the type of normative legal research. The types of approaches in this study are statutory and statutory approaches. The analysis in this study was carried out by taking an inventory of legal materials, then classifying legal materials according to the problem, then systematizing them, interpreting them in analysis, and concluding them. The results of this study prove that some of the reasons why a notary is prohibited from making notarial deeds outside the area of office are to guarantee legal certainty to the community, prevent unfair competition between notaries in carrying out their positions, and keep a notary in carrying out and being responsible for actions and certainty. law. The legal consequences of a notarial deed made outside the office area of the notary deed are inauthentic and the deed has no force and is null and void. For the notary himself, if he is found to have violated the laws and regulations regarding the position of a notary, he will receive sanctions in the form of an oral warning, or a written warning, which will then be subject to administrative sanctions. Sanctions can be in the form of temporary dismissal, or respectful discharge, even if the mistake is truly fatal and is proven to have violated the applicable rules and laws, sanctions can be given in the form of dishonorable dismissal.